Occurrence of Salmonella sp in laying hens - Gama, NMSQ (2003)
This study was carried out to investigate the presence of Salmonella sp in flocks of white laying hens. In different farms, the transport boxes of twelve flocks were inspected at arrival for the presence of Salmonella. Four positive (A, B, L and M) and one negative (I) flocks were monitored at each four weeks using bacteriological examination of cecal fresh feces up to 52 weeks. Birds were also evaluated at 52 weeks, when 500 eggs were taken randomly, and at 76 weeks, after forced molt. Salmonella enterica serovar Enteritidis and S. enterica rough strain were isolated from the transport boxes of the four positive flocks (flocks A, B, L and M). Salmonella sp was not isolated from the transport boxes or from the feces after 76 weeks-old in flock I. Salmonella sp was isolated in the 1st, 11th, 34th, 42nd and 76th weeks from flock A; in the 1st, 4th, 11th and 76th weeks from flock B; in the first week and in the 17th to 52nd weeks from flock L; and in the 1st and 76th weeks from flock M. S. Enteritidis, S. enterica rough strain and Salmonella enterica serovar Infantis were isolated from the four positive flocks. Besides, Salmonella enterica serovar Javiana was isolated from flocks B and L, and Salmonella enterica serovar Mbandaka was isolated from flock L. Eggs produced by flock A and by flock L were contaminated with S. Enteritidis and S. enterica rough strain. According to these results, Salmonella-infected flocks may produce contaminated eggs.